The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1108/09578230610704828
|View full text |Cite
|
Sign up to set email alerts
|

Proximate sources of collective teacher efficacy

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
1
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 25 publications
6
52
1
9
Order By: Relevance
“…Adams and Forsyth (2006) found that contextual factors like school structure, student SES, and grade level influenced the cognitive processing of teachers' perceptions of school-level collective efficacy. Bruce and Ross (2008) collected data from multiple sources (teacher observation, teacher self-report, and peer coaching summaries) to explore how the sources of teacher self-efficacy operated in a group of 12 elementary school teachers.…”
Section: Sources Of Teacher Efficacymentioning
confidence: 98%
“…Adams and Forsyth (2006) found that contextual factors like school structure, student SES, and grade level influenced the cognitive processing of teachers' perceptions of school-level collective efficacy. Bruce and Ross (2008) collected data from multiple sources (teacher observation, teacher self-report, and peer coaching summaries) to explore how the sources of teacher self-efficacy operated in a group of 12 elementary school teachers.…”
Section: Sources Of Teacher Efficacymentioning
confidence: 98%
“…Teachers in the current study were under pressure to improve academic performance with their at-risk students at underperforming schools. Adams and Forsyth (2006) discussed that teachers may have the tools to teach, but it is the application of their tools in specific contexts that leads to effective teaching and student learning. Investigating collective teacher efficacy at the school level, Adams and Forsyth (2006) reported that the contextual variables of socioeconomic status, supportive school structures, and school level affected their collective teacher efficacy.…”
Section: Discussionmentioning
confidence: 98%
“…Vale destacar que não se pode perder de vista fatores que devem ser considerados nesse contexto, como os aspectos sociodemográficos (Goddard, 2001), socioeconômicos (Parker, 2006;Tchannen-Moran & Barr, 2004), somados àqueles relacionados à infraestrutura, suporte pedagógico, questões sociais e políticas de cada escola (Adams &Forsyth, 2006;Skaalvik & Skaalvik, 2007).…”
Section: Eficácia Coletiva De Professoresunclassified